Impact of core laboratory assessment on treatment decisions and clinical outcomes using combined fractional flow reserve and coronary flow reserve measurements – DEFINE-FLOW core laboratory sub-study. (15th April 2023) - van de Hoef, Tim P.; Stegehuis, Valérie E.; Madera-Cambero, Maribel I.; van Royen, Niels; van der Hoeven, Nina W.; de Waard, Guus A.; Meuwissen, Martijn; Christiansen, Evald H.; Eftekhari, Ashkan; Niccoli, Giampaolo; Lockie, Tim; Matsuo, Hitoshi; et al.
Abstract: Objective: The role of combined FFR/CFR measurements in decision-making on coronary revascularization remains unclear. DEFINE-FLOW prospectively assessed the relationship of FFR/CFR agreement with 2-year major adverse cardiac event (MACE) and target vessel failure (TVF) rates, and uniquely included core-laboratory analysis of all pressure and flow tracings. We aimed to document the impact of core-laboratory analysis on lesion classification, and the relationship between core-laboratory fractional flow reserve (FFR) and coronary flow reserve (CFR) values with clinical outcomes and angina burden during follow-up. Methods: In 398 vessels (348 patients) considered for intervention, ≥1 coronary pressure/flow tracing was approved by the core-laboratory. Revascularization was performed only when both FFR(≤0.80) and CFR(<2.0) were abnormal, all others were treated medically. Results: MACE was lowest for concordant normal FFR/CFR, but was not significantly different compared with either discordant group (low FFR/normal CFR: HR:1.63; 95%CI:0.61–4.40; P  = 0.33; normal FFR/low CFR: HR:1.81; 95%CI:0.66–4.98; P  = 0.25). Moreover, MACE did not differ between discordant groups treated medically and the concordant abnormal group undergoing revascularization (normal FFR/low CFR: HR:0.63; 95%CI:0.23–1.73; P  = 0.37; normal FFR/low CFR: HR:0.70; 95%CI:0.22–2.21; P  = 0.54). Similar findings applied to TVF. Conclusions: Patients with concordantly normal FFR/CFR have very low 2-year MACE and TVF rates. Throughout follow-up, there were no differences in event rates between patients in whom revascularization was deferred due to preserved CFR despite reduced FFR, and those in whom PCI was performed due to concordantly low FFR and CFR. These findings question the need for routine revascularization in vessels showing low FFR but preserved CFR. Clinical trial registration: http://ClinicalTrials.gov NCT02328820 Highlights: Patients with both normal fractional flow reserve and coronary flow reserve have very low 2-year rates of adverse events. Event rates are equivalent between patients in whom revascularization was deferred due to preserved coronary flow reserve despite reduced fractional flow reserve, and those in whom revascularization was performed Event rates are equivalent between patients in whom revascularization was deferred due to preserved fractional flow reserve despite reduced coronary flow reserve, and those in whom revascularization was performed. These findings question the need for routine revascularization in vessels showing discordance between fractional flow reserve and coronary flow reserve